Penguatan Literasi dan Internalisasi Nilai Aswaja bagi Kader Mujahid di Era Post-Truth - M. Adi Trisna Wahyudi; Indah Listiyani; Ullya Nindyaningtyas; Nizar Zakaria; Nur Azizurrahman; M. Mahbubur Rohman; M. Rizky Akbar (Jurnal Inovasi Pengabdian Masyarakat, 2026)
The post-truth era has fundamentally altered how information circulates in Indonesian society, with hoaxes spreading six times faster than verified facts and political misinformation creating unprecedented social polarization. This community service program addresses the critical need for digital literacy and ideological reinforcement among cadres of Pergerakan Mahasiswa Islam Indonesia (PMII) Rayon Dakwah & Komunikasi. Drawing on the Aswaja (Ahlussunnah wal Jama'ah values) of tawasuth (moderation), tawazun (balance), i'tidal (justice), and tasamuh (tolerance), the program trained 45 participants through a blended learning approach combining offline workshops and digital mentoring over eight weeks. Using participatory action research methodology, the program implemented three intervention stages: needs assessment, intensive training on hoax detection and verification, and niche-based action planning. Results demonstrated significant improvements in participants' digital literacy scores (mean increase of 42%, p<0.01) and self-reported capacity to apply Aswaja principles in social media interactions. Participants successfully launched seven community-driven anti-hoax initiatives across their respective communities, including fact-checking WhatsApp groups and digital da'wah content creation. The program concludes that integrating spiritual values with technical digital skills offers a sustainable model for building cadre resilience in the post-truth era.